The Relationship between Body Image and Consumptive Behavior of Buying Cosmetics in Sales Promotion Girls in Sidoarjo: Hubungan Citra Tubuh dengan Perilaku Konsumtif Pembelian Kosmetik pada Sales Promotion Girl di Sidoarjo - Krismadani, Meinita Panca; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between body image and consumptive behavior in purchasing cosmetics at sales promotion girl (SPG) in Sidoarjo. This study uses a quantitative research method with a correlational approach and uses a scale measuring instrument, namely the body image scale and the consumptive behavior scale. The sample in this study was 100 people from the female population who were taken using a simple random sampling technique, namely sampling by setting special characteristics that are in accordance with the research objectives so that they are expected to answer research problems. Data analysis was carried out using a body image scale and a consumptive behavior scale using SPSS 25.0 for windows. . The results of data analysis showed a correlation coefficient of 0.394 which was declared positive with a significance of 0.000 <0.05. R square value of 0.12 indicates that body image has an effect of 12% on consumptive behavior. The remaining 88% of the percentage of the influence of consumptive behavior variables is influenced by other factors.